2011
DOI: 10.1371/journal.pone.0017304
|View full text |Cite
|
Sign up to set email alerts
|

A Melodic Contour Repeatedly Experienced by Human Near-Term Fetuses Elicits a Profound Cardiac Reaction One Month after Birth

Abstract: BackgroundHuman hearing develops progressively during the last trimester of gestation. Near-term fetuses can discriminate acoustic features, such as frequencies and spectra, and process complex auditory streams. Fetal and neonatal studies show that they can remember frequently recurring sounds. However, existing data can only show retention intervals up to several days after birth.Methodology/Principal FindingsHere we show that auditory memories can last at least six weeks. Experimental fetuses were given prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
98
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 80 publications
4
98
1
2
Order By: Relevance
“…We have reported that changes in fetal heart rate and motor activity to maternal reading aloud (Cohort VIII) appear to be a response to variation in normal maternal speech patterns which were partially dependent on whether women had been previously speaking naturally (Voegtline, DiPietro, Costigan, & Pater, 2013). Sontag and colleagues noted a fetal response to music that was independent from the maternal response (Sontag, Steele, & Lewis, 1969) and there has been resurgence in fetal response to and retention of musical passages (Granier-Deferre, Bassereau, Ribeiro, Jacquet, & Decasper, 2011; Partanen, Kujala, Tervaniemi, & Huotilainen, 2013). …”
Section: Chapter 12 General Discussionmentioning
confidence: 99%
“…We have reported that changes in fetal heart rate and motor activity to maternal reading aloud (Cohort VIII) appear to be a response to variation in normal maternal speech patterns which were partially dependent on whether women had been previously speaking naturally (Voegtline, DiPietro, Costigan, & Pater, 2013). Sontag and colleagues noted a fetal response to music that was independent from the maternal response (Sontag, Steele, & Lewis, 1969) and there has been resurgence in fetal response to and retention of musical passages (Granier-Deferre, Bassereau, Ribeiro, Jacquet, & Decasper, 2011; Partanen, Kujala, Tervaniemi, & Huotilainen, 2013). …”
Section: Chapter 12 General Discussionmentioning
confidence: 99%
“…auditory | brain | mother's voice | heartbeat | preterm newborns O ne of the first acoustic stimuli we are exposed to before birth is the voice of the mother and the sounds of her heartbeat. As fetuses, we have substantial capacity for auditory learning and memory already in utero (1)(2)(3)(4)(5), and we are particularly tuned to acoustic cues from our mother (6)(7)(8)(9). Previous research suggests that the innate preference for mother's voice shapes the developmental trajectory of the brain (10,11).…”
mentioning
confidence: 99%
“…For example, fetuses habituate to the native language of the environment or of the mother (11,12), familiar melodies (13) or fragments of stories heard during pregnancy (14), and even the mother's voice (15). In addition to learning-based habituation involving the laterobasal amygdala only (16), fetuses, for example, react differently to native and nonnative vowels (17) or familiar and unfamiliar melodic contours (18) and discriminate between different vowels of their native language (19). This capability for fine-tuned auditory processing and discrimination suggests that memory traces lasting for several days in the auditory cortex (20) are formed as a result of fetal learning.…”
mentioning
confidence: 99%